2018
DOI: 10.1080/16549716.2018.1475039
|View full text |Cite
|
Sign up to set email alerts
|

Motivations of South African physicians specialising in public health

Abstract: Background: South African physicians can specialise in public health through a four-year ‘registrar’ programme. Despite national health policies that seemingly value public health (PH) approaches, the Public Health Medicine (PHM) speciality is largely invisible in the health services. Nevertheless, many physicians enrol for specialist training. Objectives: This study investigated physicians’ motivations for specialising in PHM, their intended career paths, perceptions of training, and perspectives about the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 20 publications
(30 reference statements)
2
10
0
Order By: Relevance
“…Most specialized to contribute to social change and to impact on health services, thus maximizing population level health outcomes and service quality. This motivation is consistent with findings from a SA PHM registrar study (10) and a New Zealand (NZ) study of PHM specialists (30). PH approaches are underpinned by values and concerns for social justice (3134).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Most specialized to contribute to social change and to impact on health services, thus maximizing population level health outcomes and service quality. This motivation is consistent with findings from a SA PHM registrar study (10) and a New Zealand (NZ) study of PHM specialists (30). PH approaches are underpinned by values and concerns for social justice (3134).…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with a number of other studies, including a study of South African PHM registrars (10), PH practice in the UK (48), the USA (49), and Switzerland (50), as well as field epidemiology masters' programs in LMICs (51, 52), specialists in this study valued competencies in epidemiology, surveillance, and communicable disease control. They highlighted placements in hospital management, health informatics, and disease programs, which developed their skills in project management, policy analysis, and planning as core PH competencies.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Previous research demonstrated that physicians are largely drawn to specialising in PHM by their commitment to social justice and desire to transform the health system, so that public sector health services address the health needs of the public and communities. [3]…”
Section: Introductionmentioning
confidence: 99%